A influência do processo inflamatório nas convulsões e no déficit cognitivo induzidos pelo ácido glutárico em ratos jovens - Magni, Danieli Valnes (2011)
Glutaric acidemia type I (GA-I) is an inborn error of metabolism (EIM), characterized biochemically by major accumulation of glutaric acid (GA) and pathologically by a characteristic striatal degeneration. The clinical manifestations are mainly neurological and develop during childhood (up to 5 years old). Among these changes, there are the seizures and cognitive deficits, which may be precipitated by infectious processes. From this, the first hypothesis to be tested in this study was to investigate whether lipopolysaccharide E. coli 055 B5 serotype (LPS; 2 mg/Kg; i.p.), an inflammatory agent, could facilitate seizures induced by GA in young rats (21 days of life). For this, firstly it was determined the acute dose of intrastriatal GA (1.3 μmol/striatum) that cause behavioral and electroencephalographic (EEG) seizures in young rats. Moreover, it was shown that LPS administration 3 hours before GA intrastriatal injection did not change the seizures, but when LPS was administered 6 hours before the GA, it reduced the latency and increased the duration of behavioral and EEG seizures induced by GA in young rats. It also was observed that LPS injection caused an initial drop in rectal temperature of young rats (up to 2 hours), followed by a rise in temperature that started at 3 hours and remained high until 6 hours after LPS injection. Furthermore, it was shown that LPS injection 3 and 6 hours before intrastriatal injection of GA caused an increase in striatal levels of IL-1β in young rats, and this increase was statistically higher in 6 than in 3 hours. In addition, it was observed that the increase in IL-1β striatal levels, caused by LPS administration, positively correlated with total time of seizures. Finally, it was observed that previous use of IL-1β antibody prevented the latency reduction and the increased duration of seizures caused by LPS administration 6 h before intrastriatal injection of GA in young rats. Thus, these findings suggest that the signaling of IL-1β present in inflammation produced by LPS contributes significantly to neuronal hyperexcitability, and thus to reduce latency and increase the duration of seizures induced by GA. Therefore, pharmacological treatments that block the specific functions or overproduction of IL-1β in GA-I, may represent an unconventional strategy to treat this condition. However, clinical studies should be conducted to evaluate the effectiveness of treatment in glutaricoacidemic patients with convulsions. Since patients with GA-I have other important neurological changes addition to the seizures, as cognitive impairments, the second hypothesis to be tested in this study was to determine whether chronic treatment with GA (5 μmol/g; s.c.; twice per day; from the 5th to the 28th day of life) could cause spatial memory impairment in young rats, and verify whether the inflammation produced by LPS (2 mg/Kg; i.p.; one per day; from the 25th to the 28th day of life) could facilitate the cognitive deficit induced by GA. In addition, it also was evaluated the possible impact of these treatments on functional and structural changes in the hippocampus of these animals. Initially it was shown that chronic treatment with GA, as well as the treatments with LPS and GA-LPS, caused a deficit in spatial learning of young rats. However, it was demonstrated that the treatment with GA-LPS produced a greater impairment in spatial memory compared to other treatments. In addition, it was observed that none of the treatments affected weight or locomotor activity/exploratory of animals. It also was shown that chronic treatment with GA, as well as treatments with LPS and GA-LPS, increased the hippocampal levels of IL-1β and TNF-α in young rats. Furthermore, it was demonstrated that treatments with GA, LPS and GA-LPS caused a reduction in total hippocampal volume of young rats. Finally it was observed that treatments with GA, LPS and GA-LPS caused a reduction of α1 subunit activity of Na+,K+-ATPase enzyme. On the other hand, it was shown that treatments with GA and LPS caused an increase in activity of α2/3 subunits of the enzyme. Thus, only treatment with GA-LPS showed a reduction in total activity of Na+,K+-ATPase in the hippocampus of young rats. These data indicate that the impairment in spatial learning observed in rats treated with GA, LPS and GA-LPS was due to increased levels of inflammatory cytokines, the reduction in hippocampal volume and the inhibition of α1 subunit activity of Na+,K+-ATPase enzyme. However, the worsening in spatial memory observed in rats treated with GA-LPS was due to inhibition of total activity of Na+,K+-ATPase, which was specific α2/3 isoforms, since only this group showed no compensatory response the activity of these subunits. Therefore, this second part of the study showed that chronic treatment with GA caused a deficit in spatial learning in young rats, and that the presence of an inflammatory process increased the impairment in spatial memory induced by GA alone. Thus, understanding the mechanisms involved in seizures and cognitive deficits observed in patients with GA-I in the presence of an inflammatory process is important for the development of new therapies to treat this condition, as well as other diseases associated with the presence of inflammatory mediators.